2011
DOI: 10.1126/science.1200605
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Continuous Electric Dipole Rotation in Flux-Closure Domains in Ferroelectric Pb(Zr,Ti)O 3

Abstract: Low-dimensional ferroelectric structures are a promising basis for the next generation of ultrahigh-density nonvolatile memory devices. Depolarization fields, created by incompletely compensated charges at the surfaces and interfaces, depress the polarization of such structures. Theory suggests that under conditions of uncompensated surface charges, local dipoles can organize in flux-closure structures in thin films and vortex structures in nano-sized ferroelectrics, reducing depolarization fields. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
335
1
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(353 citation statements)
references
References 34 publications
15
335
1
2
Order By: Relevance
“…The spatial splitting of the flux-closure objects found here suggests an intolerance to dipole misalignment at all length scales. Thus, if the Srolovitz and Scott treatment is robust, the continuous polar rotation previously seen by aberration corrected microscopy [22,23] may be relatively uncommon, even in ferroelectric compositions close to morphotropic phase boundaries (as investigated here).…”
mentioning
confidence: 72%
“…The spatial splitting of the flux-closure objects found here suggests an intolerance to dipole misalignment at all length scales. Thus, if the Srolovitz and Scott treatment is robust, the continuous polar rotation previously seen by aberration corrected microscopy [22,23] may be relatively uncommon, even in ferroelectric compositions close to morphotropic phase boundaries (as investigated here).…”
mentioning
confidence: 72%
“…This is due to diffuse nucleation and growth of the reverse domain on the domain walls (Figure 6a), shown previously as a growth mechanism in bulk prototypical systems under an activation field using a Landau-Ginzburg-Devonshire model [47]. This first presents by the distortion of the 180 • domain wall alignment with (100) p planes (Figure 6a-d), so-called 'wandering' [5,6]. Here we observed that, with further temperature increases leading to polarisation reduction, the degree of the anisotropy increases resulting in the domain wall pattern changing from linear stripe domains into nanobubble domains (Figure 6e).…”
Section: New High Temperature Nanobubble Domain Morphologymentioning
confidence: 99%
“…Recent direct observation of so-called wandering domain walls in thin films [5], whereby the direction of the domain wall tangent significantly varies along the wall length, and the ability to control the direction of the domain wall suggests viable mechanisms for tuning intrinsic ferroelectric and piezoelectric properties [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Exotic dipole arrangements have been evidenced but their formation remains not fully understood. Recently, complex domain structures have also been observed to occur spontaneously at grain boundaries (in PZT films) 21 , and heterointerfaces in thin ferroelectric films (of PZT and BiFeO 3 ) 22,23 . First results on their control by applying external electric fields (in PZT 21 and BiFeO 3 (ref.…”
mentioning
confidence: 99%